2020
DOI: 10.1111/pai.13402
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of chronic granulomatous disease ‐ Conventional treatment vs stem cell transplantation

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Randomized, placebo-controlled trials followed for interferon gamma [ 21 ] and itraconazole [ 18 ]. Bone marrow or stem cell transplantation can be curative [ 22 , 23 ], while gene therapy (reviewed in [ 24 ]) remains under investigation as a curative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized, placebo-controlled trials followed for interferon gamma [ 21 ] and itraconazole [ 18 ]. Bone marrow or stem cell transplantation can be curative [ 22 , 23 ], while gene therapy (reviewed in [ 24 ]) remains under investigation as a curative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional treatment for CGD is antifungal and antibacterial prophylaxis with azoles and cotrimoxazole, and immunosuppressive therapy (27,28). Prophylaxis leads to a significant reduction in death rates, but infections reportedly occur at a rate of 0.26-0.64 per patient-year (29,30), whose cumulative lifetime risk for aspergillosis of 20-40% being the leading cause of death (27). Martire et al reported the median lifespan of CGD patients receiving conventional treatment to be 30-40 years (29), which was mainly relied on the NADPH oxidase's residual activity (5).…”
Section: Discussionmentioning
confidence: 99%
“…Martire et al reported the median lifespan of CGD patients receiving conventional treatment to be 30-40 years (29), which was mainly relied on the NADPH oxidase's residual activity (5). Other treatment options, such as long-term use of corticosteroids (which are immunosuppressants), further increase the risk of infections and failure to thrive (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematopoietic stem cell transplantation is the only definitive treatment that can cure CGD. The third commented article in this editorial is a retrospective study by Dedieu and colleagues from Berlin on the benefice of stem cell transplantation in the treatment of CGD 14 . They reviewed data from 104 CGD patients of whom 50 were treated by stem cell transplantation.…”
mentioning
confidence: 99%